Cinderella. - Walt Disney Company (New York : Gallery Books ; Greenwich, Conn. : Twin Books, 1986)
Retells the familiar tale of a poor young girl who marries a prince with the help of a fairy godmother.
Based on the Walt Disney movie.
At head of title: Walt Disney.
Keywords: Folklore; Fairy tales; Folklore; Fairy tales